Managing Motherhood: How Incarcerated Mothers Negotiate Maternal Role-Identities with Their Children’s Caregivers - Cunningham Stringer, Ebonie (Women & criminal justice, 2020)
Women’s incarceration rates have increased dramatically within the last 40 years. Many of the women who find themselves in the grips of confinement are mothers. Maternity can be central to women’s identities, making them reluctant to relinquish mothering roles once they become incarcerated. When women serve time, they can no longer be directly responsible for day-to-day caregiving for their young children. Thus, children are often placed in the care of proxy caregivers. Notwithstanding, many women retain their maternal identities and wish to engage as mothers while they are incarcerated. As such, women must manage motherhood with and through their children’s caregivers. Using group interviews, this study investigates how maternity is managed from prison with children’s caregivers. Findings reveal the strategies women employ to maintain their role-identities as mothers while serving time. Policy implications are discussed.